Ursolic acid represses influenza A virus-triggered inflammation and oxidative stress in A549 cells by modulating the miR-34c-5p/TLR5 axis. (September 2022) - Wei, Xing; Lan, Yuying; Nong, Zhifei; Li, Chongjin; Feng, Zhiqiong; Mei, Xiaoping; Zhai, Yang; Zou, Min
Highlights: UA inhibited the inflammatory response and oxidative stress of IAV-induced A549 cells. UA promoted miR-34c-5p expression by reducing its promoter methylation. TLR5 was a direct target of miR-34c5p. miR-34c-5 was participated in the regulation of UA on IAV-induced inflammatory injury. Abstract: Background: Ursolic acid (UA) is a pentacyclic triterpenoid compound with a wide range of anti-tumor, anti-inflammatory, hypotensive and other pharmacological effects. Here, the biological roles and regulatory mechanisms of UA in influenza A virus (IAV)-treated A549 cells were investigated. Method: The cytotoxic impacts of UA on A549 cells with or without IAV treatment were determined using MTT and LDH assays. The inflammatory responses and oxidative stress of IAV-treated A549 cells were measured by RT–qPCR, ELISA, DCFH-DA probe, and colorimetric assays. A dual luciferase assay was carried out to validate the molecular interaction between miR-34c-5p and TLR5. Promoter methylation was detected by MSP experiment. Methylation-related proteins were quantified by western blot. Virus replication was assessed by TCID50 and western blot assays. Results: UA significantly ameliorated IAV-triggered cell injury and inflammatory response, virus replication and oxidative stress by elevating cell viability, ROS level and the activities of SOD and GSH-Px but reducing the LDH, MDA, and TCID50 values and the expression of virus-related proteins (NP) and cytokines (TNF-α, IL-1β, IL-6, and IL-18). Moreover, UA promoted miR-34c-5p expression by repressing DNMTs-mediated methylation. TLR5 was verified to be a direct target of miR-34c-5p and could be downregulated by UA. Rescue experiments revealed that silencing miR-34c-5p diminished the regulatory roles of UA in IAV-treated A549 cells. Conclusion: Our data elucidated that UA attenuated IAV-triggered inflammatory responses and oxidative stress in A549 cells by regulating the miR-34c-5p/TLR5 axis, suggesting that UA plays a protective role in IAV-induced pneumonia.